Acetylator phenotypes in Papua New Guinea. Issue 1 (February 1983) - Penketh, R J A; Gibney, S F A; Nurse, G T; Hopkinson, D A
Abstract : Acetylator phenotypes have been determined in 139 unrelated subjects from the hitherto untested populations of Papua New Guinea, and their relevance to current antituberculous isoniazid chemotherapy is discussed.